Highly Efficient PANI-WH Novel Composite for Remediation of Ni(II), Pb(II), and Cu(II) From Wastewater - Arsalan, Muhammad; Siddique, Imran; Awais, Azka; Baoji, Miao; Khan, Ilyas; Badran, Mohamed; Mousa, Abd Allah A. (Frontiers in Environmental Science, 2022)
The present study comprises the synthesis of a novel composite polyaniline-wheat husk (PANI-WH) and the adsorption of heavy metals (Cu, Pb, and Ni) by using this composite. Characterizations such as SEM of the composite were used to check the chemical composition, state (XPS), crystallographic nature (XRD), and functional groups (FT-IR) of the novel composite before and after the adsorption of heavy metals. The results indicate that the adsorption performance of the PANI-WH novel composite (on heavy metals) is good with excellent binding capacity of 155 mg g−1 for Ni, 95 mg g−1 for Cu, and 110 mg g−1 for Pb. The PANI-WH novel composite shows maximum adsorption at optimum conditions. The remediation capacity of heavy metals was observed up to 99% by using the PANI-WH composite. The present study also involves kinetic, thermodynamic, and isotherm studies, showing that the adsorption of heavy metals is increased by using the PANI-WH composite. The composite material used in this work comes from industrial/agricultural by-products which provide a twofold benefit of not only providing a means of treating water but also an effective method of utilization of these by-products, which otherwise form an additional waste stream. The PANI-WH shows good stability and reusability. In future, the PANI-WH composite can be used for the detection of other heavy metals.